Homosocial shelters and the business of masculinity in Roberto Arlt's El juguete rabioso (Anclajes, 2025)
The humble social origin and the difficult economic situation suffered by Silvio Astier, the protagonist of Roberto Arlt’s novel El juguete rabioso (1926), obstruct his access to culture and keep him on the margins of certain social practices and conventions. Among them is the young man's inability to satisfy the standards of masculinity imposed by the hetero-patriarchal society of the time, often linked to the agency granted by possessing purchasing power. Unable to symbolically constitute himself as a “man,” Astier stagnates in an adolescent limbo that brings him frustration and surrounds him with cynicism. To counteract this precarious status, the boy develops strong homosocial ties with other male characters in whom he seeks refuge. This article offers a rereading of Roberto Arlt’s El juguete rabioso based on compound articulating axes ignored in critical approaches to this work, especially dealing with the intersection between social class and gender issues.
Keywords: Roberto Arlt; Argentinean literature; Gender studies; Homosociality; 20th century